Rora Regulates Neutrophil Migration and Activation in Zebrafish - Hsu, Alan Y.; Wang, Tianqi; Syahirah, Ramizah; Liu, Sheng; Li, Kailing; Zhang, Weiwei; Wang, Jiao; Cao, Ziming; Tian, Simon; Matosevic, Sandro; Staiger, Christopher J.; Wan, Jun; et al. (Frontiers in Immunology, 2022)
Neutrophil migration and activation are essential for defense against pathogens. However, this process may also lead to collateral tissue injury. We used microRNA overexpression as a platform and discovered protein-coding genes that regulate neutrophil migration. Here we show that miR-99 decreased the chemotaxis of zebrafish neutrophils and human neutrophil-like cells. In zebrafish neutrophils, miR-99 directly targets the transcriptional factor RAR-related orphan receptor alpha (roraa). Inhibiting RORα, but not the closely related RORγ, reduced chemotaxis of zebrafish and primary human neutrophils without causing cell death, and increased susceptibility of zebrafish to bacterial infection. At the transcriptional level, RORα regulates transmembrane signaling receptor activity and protein phosphorylation pathways. Our results, therefore, reveal previously unknown functions of miR-99 and RORα in regulating neutrophil migration and anti-microbial defense.